2015
DOI: 10.1136/bcr-2015-210282
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and dissociation of bipolar hip hemiarthroplasty

Abstract: Hemiarthroplasty of the hip is a commonly performed procedure for subcapital neck of femur fractures. Dislocation of the hemiarthroplasty is a recognised but uncommon complication. Dislocations can be complicated by the uncoupling or dissociation of the femoral head component from the femoral stem. Dissociations are rare and require open reduction. We present a case of a patient with a hip hemiarthroplasty dislocation and dissociation subsequent to a fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Dissociation is rare and has been reported in only a few case reports [4,7,8,13,16]. The reasons for disassociation after hemiarthroplasty have been reported as component selection and alignment, surgical technique, and patient factors [4,7,8,11,13,15,16]. Varley and Parker [25] reported that dissociations accounted for 12% of all dislocations in bipolar prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissociation is rare and has been reported in only a few case reports [4,7,8,13,16]. The reasons for disassociation after hemiarthroplasty have been reported as component selection and alignment, surgical technique, and patient factors [4,7,8,11,13,15,16]. Varley and Parker [25] reported that dissociations accounted for 12% of all dislocations in bipolar prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…We found little information regarding this rare and serious complication except for a few case reports [4,7,8,13,16].…”
Section: Introductionmentioning
confidence: 95%
“…Dislocation of the hip joint after THA is one of the major side complications (2% - 4% after primary total hip arthroplasty) [2,39] and its causes have been studied previously [5,720,3942]. Among patient related factors, the presence of neuromuscular conditions, such as cerebral palsy, muscle dystrophy, dementia and Parkinson’s disease, is one of the main risk factors [39,43]. More dislocations were found with patients older than 80 years [43], patients with a femoral neck fracture as the primary diagnosis [40,42] and patients with an ASA (American Society of Anesthesiologists) score of 3 or 4 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Among patient related factors, the presence of neuromuscular conditions, such as cerebral palsy, muscle dystrophy, dementia and Parkinson’s disease, is one of the main risk factors [39,43]. More dislocations were found with patients older than 80 years [43], patients with a femoral neck fracture as the primary diagnosis [40,42] and patients with an ASA (American Society of Anesthesiologists) score of 3 or 4 [40]. Among procedure related factors, the measured parameters of component positions, a cup inclination out of the range of 40° ± 10°, a cup anteversion of less than 10° or more than 35°, a stem anteversion out of the range of 14.8° ± 6,01° and a height of hip rotation center outside the range of 2.16 mm ± 9.11 mm, increased the risk of dislocation [8,9,40].…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar hip hemiarthroplasty for subcapital neck of femur fractures is a commonly performed procedure [ 1 ]. Dislocation after bipolar hip hemiarthroplasty is one of the serious complications, which not only combines the problem of difficult reduction but also may lead to increased mortality and morbidity in patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%